2000
DOI: 10.1016/s0364-0213(00)00023-9
|View full text |Cite
|
Sign up to set email alerts
|

Toward a science of other minds: escaping the argument by analogy

Abstract: Since Darwin, the idea of psychological continuity between humans and other animals has dominated theory and research in investigating the minds of other species. Indeed, the field of comparative psychology was founded on two assumptions. First, it was assumed that introspection could provide humans with reliable knowledge about the causal connection between specific mental states and specific behaviors. Second, it was assumed that in those cases in which other species exhibited behaviors similar to our own, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 115 publications
0
41
0
1
Order By: Relevance
“…In addition, both pieces of food were in the open so that subjects could not rely on any kind of preference for food around barriers (Povinelli, Bering, & Giambrone, 2000). By choosing the opaque tunnel, subjects were able to conceal just the initial reaching for the food, but this was enough to impede the experimenter from reacting in time.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both pieces of food were in the open so that subjects could not rely on any kind of preference for food around barriers (Povinelli, Bering, & Giambrone, 2000). By choosing the opaque tunnel, subjects were able to conceal just the initial reaching for the food, but this was enough to impede the experimenter from reacting in time.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, several recent studies performed by our group have demonstrated the important role played by the right inferior parietal cortex when the self takes the perspective of others [11,21,22,29,75] even at the conceptual level [76]. It is interesting to recall that according to several theorists, empathizing not only necessitates a sharing of affects, but a minimal distinction between the self and the other is also mandatory [23,[55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74]. Results of the present study, therefore, lead us to speculate that when subjects covertly simulate the narrative content of a sad story with the intention of rating their affinity for the communicator (i.e.…”
Section: Main Effect Of the Narrative Content Of The Storiesmentioning
confidence: 99%
“…While earlier accounts have often stressed the key role of theory of mind, [18][19][20] more recent results suggest that apes do have simple elements of that theory, such as an emerging understanding of what others are attending to and intending, although these capacities are primarily expressed in competitive contexts 11 (but see Penn and Povinelli 21 ). Such findings shift the focus onto the apparently central role played by shared intentionality, 22,23 which has now been identified as the fundamental source for the majority, if not all, of our unique cognitive achievements.…”
mentioning
confidence: 99%